Experimental study on the effect of sustained axial compression load at early age on the tensile strength of concrete during late splitting. Issue 7 (April 2020) - Jinping, Zhuang; Chen, Jianxing; Cai, Xuefeng; Qiu, Hao
Abstract: In order to study the effect of early-stage concrete loading on the tensile strength of the later splitting, a total of 11 series of specimens were designed. Through the continuous pressure in early age, the effects of early bearing axial compression ratio, loaded time and concrete strength on the tensile strength of concrete during splitting were discussed.A set of sustained pressure device was set up, through which six concrete specimens could be applied continuous pressure force together. The test results show, when compression ratio is less than 0.5, the sustained pressure at early age has positive effect on the late splitting tensile strength. The increase range in the experimental parameters is between 3.7% and 24.5%.